The Dynamics of Reading Kitab Kuning at Ibtida’ Level in Pesantren - Muhammad, Muhammad; Ahid, Nur; Hamidah, Ani Mar'atul (Institut Agama Islam Negeri Kediri, 2025)
Learning Kitab Kuning is a characteristic of traditional Islamic boarding school education which has an important role in preserving the classical Islamic knowledge. However, in its implementation, especially at the ibtida' level, various obstacles are often found that hinder learning activities. This study aims to identify the problems faced in the yellow book reading method in Islamic Boarding Schools, especially at the ibtida' level, and to analyze the causal factors and their impact on the learning achievements of students. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that The results of the study show that there are 4 (four) dynamics of the Kitab Kuning reading method, including (1) low basic Arabic language competency of students and a linguistic system that contrasts with Indonesian; (2) low motivation to learn of students, (3) limited quantity of teacher, and (4) there is no standardization of standard Kitab Kuning learning methods, especially at the Ibtida' level. This study recommends the need for innovation in teaching methods that are more communicative and interactive from teacher, as well as full support from the Islamic boarding school institution to be able to answer the dynamics of the Kitab Kuning reading method.